UPAYA MENINGKATKAN KEMAMPUAN PERKEMBANGAN BAHASA DENGAN INDIKATOR BERCERITA TENTANG GAMBAR - Susanti, Eka (CV Sintesia, 2024)
The existence of a kinder garten learning curriculum in which there are aspects of child development sunc as religious moral development, social emotional, language, physical motor, cognitive ad art. So in learning activities one of the aspects of language development that contains developmental indicators such as telling stories about pictures. For this reason, i discuss the problems so far by holding story telling activities but have not met satisfactory results for teachers, children and schools. I was assisted by a colleague trying to research why it could be like what happened in the discussion above. Examining the teacher’s own problems, teaching language, tools, children and supportingmaterials that are incomplete and allthe data collected, we conduct research and improvements step by step in the first second, third and third cycles. so on untill it meets success ofthe leaming activities in the. The action of implementing class action ( PTK) resuls in a satisfying learning activity and improve developmental aspects, especially the language that is being Rangs, all objektives will be achieved.